Molecular Mechanisms of mtDNA-Mediated Inflammation - Anna De Gaetano (MDPI AG, 2021)
Besides their role in cell metabolism, mitochondria display many other functions. Mitochondrial DNA (mtDNA), the own genome of the organelle, plays an important role in modulating the inflammatory immune response. When released from the mitochondrion to the cytosol, mtDNA is recognized by cGAS, a cGAMP which activates a pathway leading to enhanced expression of type I interferons, and by NLRP3 inflammasome, which promotes the activation of pro-inflammatory cytokines Interleukin-1beta and Interleukin-18. Furthermore, mtDNA can be bound by Toll-like receptor 9 in the endosome and activate a pathway that ultimately leads to the expression of pro-inflammatory cytokines. mtDNA is released in the extracellular space in different forms (free DNA, protein-bound DNA fragments) either as free circulating molecules or encapsulated in extracellular vesicles. In this review, we discussed the latest findings concerning the molecular mechanisms that regulate the release of mtDNA from mitochondria, and the mechanisms that connect mtDNA misplacement to the activation of inflammation in different pathophysiological conditions.